Planejamento experimental na otimização da extração dos frutos de Syzygium cumini (L.) skeels - Migliato, Ketylin Fernanda [UNESP]; Corrêa, Marcos Antonio [UNESP]; Salgado, Hérida Regina Nunes [UNESP]; Tognolli, João Olimpio [UNESP]; Sacramento, Luis Vitor S. [UNESP]; Mello, João Carlos Palazzo de; Mendes Giannini, Maria José Soares [UNESP]; Almeida, Ana Marisa Fusco [UNESP]; Pizzolitto, Antonio Carlos [UNESP] (Sociedade Brasileira de Química, 2011)
The aim of this study was to standardize the extractive solution of Syzygium cumini. The extractive solution was selected through a full factorial design, considering the extraction method (maceration-5-days, turbo extraction, percolation), extractor solvent (ethanol 50, 70, 96%) and plant material particle size 0.302 mm into a plant:solvent ratio (1:10), using the dried residue and antimicrobial activity determination as evaluation criteria. The tests were performed in triplicate. It appeared that the percolation is the best procedure extractive, and ethanol mixture: water (50:50) the best solvent. ANOVA analysis showed the importance of these parameters.
Factorial design of the optimization extraction of Syzygium cumini (L.) Skeels fruits
Keywords: Syzygium cumini; extraction method; factorial design